Feasibility of an Enhanced Therapy Model of Care for Hospitalized Stroke Patients. (February 2023) - Pruski, April; Lavezza, Annette; Ye, Bingqing; Langton-Frost, Nicole; Orient, Stephanie; Adeyemo, Jessica; Zink, Elizabeth K.; Daley, Kelly; Bahouth, Mona N.
Abstract : Introduction: The aim of this study was to determine the safety and feasibility of an enhanced therapy model for hospitalized stroke patients. Methods: This was a quasi-experimental cohort study of acute stroke patients from a single hospital. In the intervention group, all hospitalized patients on the acute stroke service were seen by at least two therapy disciplines daily in addition to routine stroke care. The comparison group consisted of all patients admitted to the same stroke service 1 year before who received the standard of care. The primary endpoint was the number of completed therapy sessions. Exploratory endpoints compared the length of hospital stay, hospital readmission rates, and degree of disability measured by the 90-day modified Rankin Scale score. Results: A total of 1110 records were analyzed with 553 subjects in the intervention group and 557 in the control group. The intervention group received a significantly higher number of therapy sessions. There was no significant difference in length of hospital stay. However, 30-day readmission rates were lower, and the percentage of patients who achieved a good functional outcome on the modified Rankin Scale was higher during the intervention period. Conclusion: Increasing exposure to intensive multidisciplinary therapy comparable with that of acute inpatient rehabilitation in the hospital setting is feasible and may reduce both readmission rates and disability.